Management of thoracolumbar spine fractures - Wood, Kirkham B.; Li, Weishi; Lebl, Darren S.; Ploumis, Avraam (The spine journal, 2014)
Traumatic fractures of the spine are most common at the thoracolumbar junction and can be a source of great disability. To review the most current information regarding the pathophysiology, injury pattern, treatment options, and outcomes. Literature review. Relevant articles, textbook chapters, and abstracts covering thoracolumbar spine fractures with and without neurologic deficit from 1960 to the present were reviewed. The thoracolumbar spine represents a unique system from a skeletal as well as neurological standpoint. The rigid rib-bearing thoracic spine articulates with the more mobile lumbar spine at the thoracolumbar junction (T10 - L2), the site of most fractures. A complete examination includes a careful neurologic examination of both motor and sensory systems. CT scans best describe bony detail while MRI is most efficient at describing soft tissues and neurological structures. The most recent classification system is that of the new Thoracolumbar Injury Classification and Severity Score. The different fracture types include compression fractures, burst fractures - both stable and unstable -, flexion-distraction injuries and fracture dislocations. Their treatment, both operative and non-operative depends on the degree of bony compromise, neurological involvement, and the integrity of the posterior ligamentous complex. Minimally invasive approaches to the care of thoracolumbar injuries have become more popular, thus, the evidence regarding their efficacy is presented. Finally, the treatment of osteoporotic fractures of the thoracolumbar spine is reviewed, including vertebroplasty and kyphoplasty, their risks and controversies, and senile burst fractures, as well. Thoracolumbar spine fractures remain a significant source of potential morbidity. Advances in treatment have minimized the invasiveness of our surgery and in certain stable situations, eliminated it all together.